1967
DOI: 10.1111/j.1939-0025.1967.tb00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors in phenylketonuria.

Abstract: Psychosocial factors in phenylketonuria were studied through observations of parent‐child interaction in a simulated eating situation, questionnaires tapping parental understanding of the disease and interviews exploring problems in diet control. The importance of the findings to the prediction of outcome, management and understanding of the disorder was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…This study documents and emphasizes the importance of certain psychosocial influences in the mental retardation and behavioral disturbance of children with PKU as was previously suggested by the clinical report of Bjornson (1964) and the findings from studies by Wood et al (1967) and Keleske et al (1967). Most important, the early experiences of sensory deprivation and immobilization identified and studied have implications for prog-nosis, prevention, and treatment of children with PKU.…”
Section: Conclusion and Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This study documents and emphasizes the importance of certain psychosocial influences in the mental retardation and behavioral disturbance of children with PKU as was previously suggested by the clinical report of Bjornson (1964) and the findings from studies by Wood et al (1967) and Keleske et al (1967). Most important, the early experiences of sensory deprivation and immobilization identified and studied have implications for prog-nosis, prevention, and treatment of children with PKU.…”
Section: Conclusion and Discussionsupporting
confidence: 73%
“…Evidence of the importance of psychosocial influences was provided by Wood, Friedman, and Steisel (1967) who emphasized difficulties in enforcement of the stringent diet, the influence of the parents' distorted understanding of PKU, and the impact upon the parents of the implicit or explicit idea of genetic impairment. Direct observations of parents and their children in a simulated eating situation suggested that the parents' feelings of desperation and helplessness created a pervasive need to monitor, control, and restrict not only the child's eating behavior but his exploratory and play behavior as well.…”
mentioning
confidence: 99%
“…Patients with untreated PKU are also known to demonstrate severe behavioral disturbances including psychotic, autistic, and aggressive disorders. 27 The degree of intellectual deficiency plays certainly an important role with regard to the development and presentation of autism spectrum disorder–like characteristics; autism spectrum disorder symptoms are likely to appear more severe when intellectual deficiency is associated. There is also difficulty in differentiating autism when it is accompanied by profound intellectual deficiency; this difficulty applies mainly to the Autism Diagnostic Interview–Revised 20 but little to the Childhood Autism Rating Scale.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Psychiatric Patients with untreated PKU have been shown to demonstrate severe behavioral disturbances, including psychotic, autistic, and aggressive disorders. 53 Følling characterized such patients as anxious, shy, angry, prone to temper tantrums, irritated, unsociable, and catatonic. 7 The introduction of newborn screening and widespread early initiation of dietary treatment led to elimination of the most severe psychiatric disturbances; however, more subtle psychiatric findings have been identified in diettreated patients.…”
Section: Cognitive and Psychiatric Symptoms Of Pku Cognitivementioning
confidence: 99%